PENGGUNAAN GIMKIT SEBAGAI ALAT EVALUASI INTERAKTIF UNTUK MENINGKATKAN MINAT BELAJAR PADA PESERTA DIDIK KELAS V UPT SPF SDN PARANG TAMBUNG 1 MAKASSAR - Nurtisa Amelia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to increase learning interest in class V students of UPT SPF SDN Parang Tambung 1 Makassar through the use of Gimkit as an interactive evaluation tool. The research method used is Classroom Action Research (PTK) with two cycles, which involves planning, implementation, observation, and reflection. Each cycle consists of four meetings with a focus on using Gimkits to measure students' interest and engagement in the learning process. The results showed that the use of Gimkit significantly increased students' interest in learning and learning evaluation results, characterized by their high enthusiasm and involvement when using Gimkit as an evaluation tool. In the first cycle, the average interest of students was 65% to 85% at the end of the second cycle. The average score of learning evaluation results also increased from 70 to 85. Based on these results, it can be concluded that the use of Gimkit as an interactive evaluation tool is effective in increasing learning interest in class V students.